ANALISIS PENGARUH KOMPETENSI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA SWASTA YAYASAN PERGURUAN dr. WAHIDIN SUDIROHUSODO MEDAN - Simbolon, Dwi Maria (Jurnal Manajemen dan Bisnis, 2021)
This study aims to describe the effect of competence, organizational culture and work environment on the performance of junior high school teachers at the educational foundation dr. Wahidin Sudirohusodo Medan. This study uses a non-probability sampling method. The research respondents were all junior high school teachers at the educational foundation dr. Wahidin Sudirohusodo Medan, amounting to 75 (seventy-five) teachers using the census method. The instrument used was a questionnaire to collect data from competency variables, organizational culture variables, work environment variables, and performance variables. The data analysis technique used is the validity test, reliability test, descriptive analysis, multicollinearity test, normality test, multiple linear analysis, multiple linear correlation coefficient test, t test, F test, and calculation of the coefficient of determination. Descriptive analysis results for competency variables, organizational culture variables, work environment variables and performance variables are in the very good category. Based on the partial analysis, competence, organizational culture and work environment have a positive and significant effect on the performance of teachers in junior high schools at the educational foundation dr. Wahidin Sudirohusodo Medan. The F test shows that competency, organizational culture and work environment simultaneously influence the performance of teachers in junior high schools at the educational foundation dr. Wahidin Sudirohusodo Medan. The contribution of competency, organizational culture and work environment variables to improve teacher performance variables was 95.4%, while the remaining 4.6% was influenced by other variables not examined by the authors in this study, such as job satisfaction, motivation, work conflict, and others.